STRATEGI REKRUTMEN DAN SELEKSI YANG EFEKTIF UNTUK MENINGKATKAN KUALITAS TENAGA KERJA - Han Ratu Ananda Pratiwi; Hendra Riofita (Lembaga Pengembangan Kinerja Dosen, 2024)
Improving the quality of the workforce is a very important factor in achieving the success of an organization. The strategy implemented in recruitment and selection must be effective and be the main reason for obtaining individuals who have the skills, knowledge, and competencies that match the needs of the company in the era of increasingly tight global competition, attracting qualified individuals and having the potential to be the key to success for every organizational growth. Recruitment and selection are the initial processes that allow companies to find the right prospective employees. Recruitment and selection are two crucial processes in human resource management (HR). The success of a company in recruiting and selecting the right workforce has a direct impact on the quality of the work team, productivity, and sustainability of the organization. For this reason, an effective strategy is needed in both processes to ensure that the recruited workforce not only meets technical requirements, but also has a cultural fit with the organization. This article will discuss the strategic steps in recruitment and selection to improve the quality of the workforce.